Measurement of use value and non-use value of environmental quality consistent with general equilibrium approach - Naoki Sakamoto; Kazunori Nakajima (European Regional Science Association (ERSA), 2014)
This paper proposes the consistent method with general equilibrium models to measure use value and non-use value of large-scale change in environmental quality. First, we develop a general equilibrium model that parameters of the utility function with environmental quality as a dependent variable can be estimated on the basis of the travel cost method and the contingent variation method. Second, we examine to identify the general equilibrium impact of environmental quality by a comparative static analysis. Third, considering change in prices and income, we decompose the benefits from change in environmental quality into use value and non-use value.
Keywords: C68; Q51; Q54; 330; Computable general equilibrium models; Use value; Non-use value